(untitled) (Global Journal of Management and Business Research, 2022)
A hotel’s housekeeping department is its foundation. It not only maintains the cleanliness of the entire inn, but also contributes significantly to a variety of other activities in a lodge. Keeping track of and maintaining all of the hotel convenience and public areas is a challenge in and of itself, making it one of the inn’s most important branches. The work done by the housekeeping office has a significant impact on the tourist experience at the lodging. The study looked into the impact of housekeeping administrations and practices on customer satisfaction and repeat business. Laundry, Decor, Room Amenities, Cleanliness, Guest Satisfaction, and Repeat Business were the constructs used in the review. Cleanliness and stylistic arrangement were proven to have a positive impact